The floristic compositions of vascular epiphytes of a seasonally inundated forest on the coastal plain of Ilha do Mel Island, Brazil - de Andrade Kersten, Rodrigo (2006)
A 3 000 m2 area of seasonally inundated forest on the island of Ilha do Mel (25º30” S 48º23” W) in Paraná, Brazil, was sampled by collecting plants from all strata, using climbing equipment when necessary. The area harbors 103 species of epiphytes, in 49 genera and 20 families, of which 28 species are pteridophytes and 75 magnoliophytes (64 Liliopsida, 11 Magnoliopsida). The most common families are Orchidaceae, Bromeliaceae, Polypodiaceae and Araceae, and frequent genera are Vriesea, Epidendrum, Maxillaria, Pleurothallis and Prosthechea. Eight families were represented by one species each. Most species were classified as obligatory holoepiphytes (62%), followed by the relatively more rare preferential holoepiphytes (13%), facultative epiphytes (11%), hemiepiphytes (9%) and accidental epiphytes (6%).